EIS Evaluation of Fe, Cr, and Ni in NaVO3 at 700°C - Sotelo-Mazón, O.; Porcayo-Calderon, J.; Cuevas-Arteaga, C.; Ramos-Hernandez, J. J.; Ascencio-Gutierrez, J. A.; Martinez-Gomez, L. (Journal of Spectroscopy, 2014)
Due to the depletion of high-grade fuels and for economic reasons, use of residual fuel oil in energy generation systems is a common practice. Residual fuel oil contains sodium, vanadium, and sulphur as impurities, as well as NaCl contamination. Metallic dissolution caused by molten vanadates has been classically considered the main corrosion process involved in the degradation of alloys exposed to the combustion products of heavy fuel oils. Iron and nickel base alloys are the commercial alloys commonly used for the high temperature applications, for example, manufacture of components used in aggressive environments of gas turbines, steam boilers, and so forth. Therefore, because the main constituents of these materials are Fe, Cr, and Ni, where Cr is the element responsible for providing the corrosion resistance, in this study the electrochemical performance of Fe, Cr, and Ni in NaVO3 at 700°C in static air for 100 hours was evaluated.